The other Asian enigma: Explaining the rapid reduction of undernutrition in Bangladesh - Headey, Derek D.; Hoddinott, John F.; Ali, Disha; Tesfaye, Roman; Dereje, Mekdim (Elsevier, 2015)
Although South Asia has long been synonymous with persistent and unusually high rates of child undernutrition – the so called Asian Enigma – Bangladesh has managed to sustain a surprisingly rapid reduction in the rate of child undernutrition for at least two decades. We investigate this unheralded success through a regression and decomposition analysis of changes in child growth outcomes across five rounds of DHS surveys from 1997 to 2011. We find that rapid wealth accumulation and large gains in parental education are the two largest drivers of change, though health, sanitation, and demographic factors have played significant secondary roles.